Comparison of Urine and Genital Samples for Detecting Human Papillomavirus (HPV) in Clinical Patients. (27th March 2023) - Yang, Hui; Luo, Zhao-Yun; Lin, Fen; Li, Lie-Jun; Lu, Min; Xie, Long-Xu; Yang, Li-Ye
Abstract : Background . Human papillomavirus (HPV) is the main cause of cervical cancer. The aim of the present study was to investigate HPV DNA detection and genotyping on paired genital and urine samples and to evaluate if urine samples could be used to monitor HPV infection. Methods . Study subjects were recruited from one local hospital in Guangdong of China from September 1, 2011, to June 30, 2012. They were invited to participate if they have taken an HPV genotyping assay for clinical diagnosis of the genital-urinary disease or for a health check-up 3–5 days ago. DNA was extracted from paired genital and urine samples; genotyping was performed with the GenoArray assay. Results . A total of 250 patients were recruited, which included 203 females and 47 males. Our results showed that the overall agreement on HPV status between the paired samples was 77.1% (155/201, 95% CI: 0.713–0.829) for females, with a kappa value of 0.523 (95% CI: 0.469–0.632), while the agreement was extremely low in the paired male samples. As to individual genotyping, the greatest agreement was found for HPV16 type-specific identification in females (96.02%, 0.933–0.987), followed by the other 12 high oncogenic risk (HR-HPV) types, while the agreement for low-risk HPV detection is poor ( κ  < 0.6). Agreement between paired samples showed that HPV detection had a significantly greater concordance in the samples obtained in females than males (p  = 0.002). Moreover, the agreement for low-risk HPV detection was significantly lower as compared to HR-HPV detection (48.1% vs. 62.3%, p  = 0.044). Conclusion . Despite reduced sensitivity, HPV detection in urine closely represents the same trend that is seen with genital sampling. Urine appears to be an appropriate surrogate sample for HPV DNA detection in women with very limited access to healthcare, while the utility of urine for HPV DNA detection in males is less certain.